Correlates and importance of neglect-like symptoms in complex regional pain syndrome. Issue 5 (May 2018) - Wittayer, Matthias; Dimova, Violeta; Birklein, Frank; Schlereth, Tanja
Abstract : Abstract: Neglect-like symptoms (NLS) are frequently observed in complex regional pain syndrome (CRPS). The clinical meaning of NLS, however, is largely unknown. Therefore, this study sets out to assess the importance of NLS for patient outcome and to explore their clinical correlates. We assessed NLS in a group of 53 patients with CRPS and compared the results to 28 healthy volunteers. To define the origin of the NLS reports, we tested the subjective visual midline, performed a limb-laterality recognition test, and quantitative sensory testing. In addition, psychological and pain assessment scales were completed. Tests were analyzed with univariate and multivariate approaches. After 6 months, patients were reassessed and the influence of NLS on pain outcome was determined. Most patients reported NLS in the questionnaire, whereas subjective visual midline and limb-laterality recognition test in contrast to previous studies did not reveal perceptual disturbances. Neglect-like symptom scores were associated with pain and pain catastrophizing in acute CRPS and anxiety and thermal sensory loss in chronic CRPS. Furthermore, high NLS scores had a negative impact on pain outcome after 6 months. Our results indicate that NLS have a different meaning in acute and chronic CRPS and might be of prognostic value. Possibly, treatment should focus on reducing NLS. Abstract : Supplemental Digital Content is Available in the Text.Neglect-like symptoms have an influence on outcome in patients with complex regional pain syndrome (CRPS) and express "avoid pain" mechanisms in acute CRPS, becoming part of the disease in chronic CRPS.